Extending the Transhuman Person: Religious Practices as Cognitive Technological Enhancements - Tanton, Tobias (Religions, 2025)
Transhumanism embraces the use of technology to enhance human capabilities. In keeping with traditional theories of cognition, transhumanists typically assume that mental capacities are organism-bound (or brain-bound), and enhancement is thus achieved exclusively by modifying the human organism. However, 4E cognition challenges this assumption. Instead, understanding the mind as extended or scaffolded highlights how cognitive processes recruit environmental resources to perform their tasks. Therefore, as Andy Clark argues, cognitive enhancement is no longer restricted to modifications of the biological organism but is also achieved by using cognitive tools or niches that allow brain–body–world coalitions to perform more efficient or more sophisticated cognitive functions. Hence, humans are ‘natural-born cyborgs’ who have long been using environmental resources to enhance cognitive abilities. In this article, I extend this analysis to religion. Drawing on recent work on 4E cognition in religious practices, I argue that religious practices can themselves be understood as ‘cognitive technologies’ that count as enhancements. These insights from cognitive science serve to reframe the dialog between Christian theology and transhumanism: (1) enhancements are reframed as belonging to a long history of self-modification, rather than being the sole purview of the future, (2) humans should be understood as intrinsically technological, and (3) theologians are already in the enhancement game and, conversely, transhumanists should consider religious practices.